2010
DOI: 10.3390/en3111805
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Upgrading of Biomass Fast Pyrolysis Vapors with Nano Metal Oxides: An Analytical Py-GC/MS Study

Abstract: Fast pyrolysis of poplar wood followed with catalytic cracking of the pyrolysis vapors was performed using analytical pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). The catalysts applied in this study were nano MgO, CaO, TiO 2 , Fe 2 O 3 , NiO and ZnO. These catalysts displayed different catalytic capabilities towards the pyrolytic products. The catalysis by CaO significantly reduced the levels of phenols and anhydrosugars, and eliminated the acids, while it increased the formation of cyclopentanon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(150 citation statements)
references
References 37 publications
(48 reference statements)
11
136
1
2
Order By: Relevance
“…Nano metal oxides also exhibited good catalytic activity in bio-oil upgrading. For instance, nano MgO, CaO, TiO 2 , Fe 2 O 3 , NiO, and ZnO were used in catalytic cracking of poplar wood pyrolysis vapors in a pyrolysis tube [61]. The results indicated that CaO was the most effective catalyst in increasing the formation of hydrocarbons, reducing the production of anhydrosugars and phenols, and eliminating acids.…”
Section: Oxides Catalystsmentioning
confidence: 99%
“…Nano metal oxides also exhibited good catalytic activity in bio-oil upgrading. For instance, nano MgO, CaO, TiO 2 , Fe 2 O 3 , NiO, and ZnO were used in catalytic cracking of poplar wood pyrolysis vapors in a pyrolysis tube [61]. The results indicated that CaO was the most effective catalyst in increasing the formation of hydrocarbons, reducing the production of anhydrosugars and phenols, and eliminating acids.…”
Section: Oxides Catalystsmentioning
confidence: 99%
“…Depolymerization is the main process responsible for the decomposition of holocellulose during fast pyrolysis [56]. Qiang et al [55] reported that the depolymerization process results in the formation of various anhydrosugars (mainly levoglucosan), furans and other products, although the high content of CaO in the fuel reduces the formation of levoglucosan. The presence of calcium promotes glucose fragmentation instead of cellulose depolymerisation [56].…”
Section: Pyrolysis-gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…The mineral content in biomass also affects the quantity and quality of the products yields [53]. The literature suggests that high contents of monovalent potassium and divalent calcium in fuels are responsible for the lower organic volatile yield and may promote dehydration of holocellulose and demethoxylation of lignin units during pyrolysis [33,49,[52][53][54][55][56]. This is consistent with our findings, since Terminalia, which has the highest CaO content (41.7 wt.%) records the highest peak area % for lignin products especially for methoxy-phenols and phenols (see figure 11).…”
Section: Pyrolysis-gas Chromatography-mass Spectrometrymentioning
confidence: 99%
“…Lignin primarily consists of guaiacyl propane units, syringyl propane units, and phydroxyphenyl propane units, and it has a three-dimensional network structure (Huijgen et al 2014). A number of active functional groups, such as phenolic hydroxyl, alcoholic hydroxyl, methoxy, and carboxyl groups, leads to the high reactivity of lignin, which can be transported and converted to renewable fuels and valuable products (Lu et al 2010;Dickerson and Soria 2013).…”
Section: Introductionmentioning
confidence: 99%